2022
DOI: 10.1021/acscatal.1c04869
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Reaction Pathway of Mononuclear Iron Enzyme-Catalyzed N≡C Triple Bond Formation in Isocyanide Lipopeptide and Polyketide Biosynthesis

Abstract: Despite the diversity of reactions catalyzed by 2oxoglutarate-dependent nonheme iron (Fe/2OG) enzymes identified in recent years, only a limited number of these enzymes have been investigated in mechanistic detail. In particular, several Fe/2OGdependent enzymes capable of catalyzing isocyanide formation have been reported. While the glycine moiety has been identified as a biosynthon for the isocyanide group, how the actual conversion is effected remains obscure. To elucidate the catalytic mechanism, we charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 69 publications
2
23
0
Order By: Relevance
“…This precise substrate orientation facilitates C5–H abstraction rather than at the weaker proximal N–H bond. This C5–H bond activation and the subsequent hydroxyl rebound step align with an experimentally observed on-pathway hydroxylated intermediate. , …”
Section: Metalloenzymes That Catalyze C–h Bond Activationsupporting
confidence: 82%
See 2 more Smart Citations
“…This precise substrate orientation facilitates C5–H abstraction rather than at the weaker proximal N–H bond. This C5–H bond activation and the subsequent hydroxyl rebound step align with an experimentally observed on-pathway hydroxylated intermediate. , …”
Section: Metalloenzymes That Catalyze C–h Bond Activationsupporting
confidence: 82%
“…The array of chemical transformations performed by Fe­(II)/α-ketoglutarate-dependent oxygenases span hydroxylation, halogenation, desaturation, carbon–carbon cleavage, and more recently, isonitrile formation, , with some multifunctional nonheme iron enzymes being able to perform different reactions under different conditions. , For the well-studied halogenase SyrB2, experimental and computational investigations have revealed that the position of the substrate correlates to whether rebound of the chloride or hydroxyl is observed. , A more complete understanding of the factors governing the relative propensity toward halogenation or hydroxylation is an important prerequisite for the design of novel halogenases and synthetic mimics capable of halogenation . Computational studies suggest that SyrB1, the carrier protein that works with SyrB2, plays an essential role in halogenation selectivity by positioning the substrate deeper into the active site, where the substrate forms cooperative hydrogen bonds with the Asn123 residue (Figure ).…”
Section: Metalloenzymes That Catalyze C–h Bond Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, only 2 with trans-configuration was chemically synthesized based on the NOESY correlation between the sp 2 -methine and the nitrogen-bearing sp 3 -methine observed from both the final synthetic compound and its ester synthetic precursor (Figures S6 and S7). A previous study reported that cis -imine CABA was not recognized by SfaA to generate INBA, although this conclusion was questionable based on a recent paper from the same group, which confirmed 2 as a reaction intermediate without specifying its configuration . We further determined the kinetic parameters of ScoE toward 2 ( k cat = 21.9 ± 0.6 min –1 , K M = 369 ± 40 μM), which were comparable to CABA ( k cat = 21.9 ± 2.1 min –1 , K M = 286 ± 93 μM) as reported previously (Figure B) …”
Section: Resultsmentioning
confidence: 99%
“…During the QM/MM calculations, the QM region was studied by UB3LYP, [56][57][58] which is demonstrated to be reliable for Fe-containing metalloenzymes. [59][60][61][62][63][64][65] The all-electron basis of Def2-SVP (labeled B1) 66 was used for geometry optimizations, while the energies were further corrected with the larger basis set Def2-TZVP (labeled B2). 66 Dispersion corrections computed with Grimme's D3 method [67][68][69] were included in all QM/MM calculations.…”
Section: Methodsmentioning
confidence: 99%